Water Damage Evaluation Of Fly Ash Geopolymer Modified Binder In Asphalt Mixture - BIN JOFRI, ZAIIRUL HAFIZHAT; Mohamad Taher, Mohammad Nasir (Recent Trends in Civil Engineering and Built Environment, 2021)
Moisture damage has been a major concern for many years. It will cause stripping and accelerated the formation of potholes. Moisture are required to cause this type of damage in both liquid and vapour form, entering the pavement through infiltration of surface water by tire action, irrigation or repetitive traffic loading. In this study compacted specimens are the most common approach for checking the resistance to moisture of mixtures. The testing procedures for compact samples consist of indirect, adjusted tensile measurements (Lottman AASHTO T-283). This study are conduct to evaluate the effect of moisture on superpave mix design mixture with additive material Fly Ash Geopolymer (FAG). The material used in this study are granite aggregate and fly ash geopolymer. For the ITS value, the highest ITS value for the specimens used 9% of FAG. The highest ITSR value for the specimens used 3% of FAG. The ITSR result also shows that all the value comply with the AASHTO T-283. It can be conclude that the used of FAG in asphalt mixture with 60/70 bitumen grade can increased the resistance to moisture sensitivity. If the investigation confirms the existing belief that moisture damage is not a concern, the need for AASHTO T-283 to be used indefinitely must be questioned. The future researcher should study all the parameter to understand about stripping problem due to water damaged more precisely. Study more about the material used to improve water resistance and increase the ITSR value.